Youth entrepreneurship in the mechanism of ensuring sustainable economic growth of national economy - Khussainova, Zh.S.; Abauova, G.M.; Adilova, Zh.G.; Zhartay, Zh.M. (BUKETOV BUSINESS REVIEW, 2018)
In article are researched features of a youth entrepreneurship, it is provided data of social researches in the field. Authors recognize that development of business activity of youth is an essential factor of successful socialization of youth, effective inclusion in processes of ensuring sustainable economic growth of national economy. In article are offered also weaknesses of a youth entrepreneurship, a problem of its development are reflected in Kazakhstan strong, mechanisms of regulation and stimulation of business activity of youth. Implementation of measures of state policy for development and activization of youth business in the mechanism of industrial and innovative growth of the Republic of Kazakhstan will allow to increase efficiency and targeting of measures of support of business activity of youth that will promote eventually expansion of a share of youth business (including innovative) and to the general growth of the business sector, increase in public welfare, expansion of the middle class.